To Compare the Frequency of Fracture Consolidation in Two Versus Three Cannulated Screws Osteosynthesis of Femoral Neck Fractures - Shahzad Latif, Faheem Ahmed, Wasif Masood, Fahad Ahmed Khan, Usman Ghani Farooqi, Abdul Aleem Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: When it happens in a child or adolescent, an intracapsular femoral neck fracture can be very challenging to heal. Hip fractures are expected to rise from 1.26 million in 1990 to 2.6 million in 2025 and 4.5 million by the middle of this century, according to the latest estimates. 1 After a fixation, problems might occur for a number of various reasons, including those listed above. The initial displacement and the time and accuracy of the reduction are the most essential factors in determining the final output. Objective: To compare the frequency of fracture consolidation in two versus three cannulated screws for osteosynthesis of femoral neck fractures. Subjects and Method: In Karachi, the Al Mumtaz hospital complex hosted a total of eighty patients who met the study's eligibility criteria and agreed to participate. After being informed of the technique, patients agreed to participate. Each patient's name, age, gender, address, and phone number were entered into a database. utilizing a lottery technique, each patient was placed in one of two groups, A or B. 80 chits (40 for group A and 40 for group B) sealed in opaque envelope was put in a jar and patient was asked to pick one chit from jar and that patient was assigned to that particular group written on that chit. In group A, 40 patients were undergo osteosynthesis by using two cannulated screws, while in group B, 40 patients were undergo osteosynthesis by using three cannulated screws. All procedures were done under general anesthesia and by same surgeon’s team having minimum 5 years post qualification surgical experience. After surgery, patients were shifted to ward and was discharged. Then patients were followed-up in OPD for 3 months after surgery for assessment of fracture consolidation. Final assessment was made at 3rd month. Data was entered and analyzed through SPSS version 20. Results: In total, there were eighty people that took part in this research. Two cannulated screws were inserted into forty patients, whereas another forty patients received three screws. Patients with ages ranging from 18 to 55 were included in the study. Patients in Group 1 were on average 32.4 years old plus 8.13 years, while patients in Group 2 were on average 35.9 years old plus 9.01 years. Patients who were treated with two cannulated screws achieved fracture consolidation in 35 (87.5% of cases), but patients who were treated with three cannulated screws only experienced fracture consolidation in 20 (50%) of their instances, which is a significant difference. Conclusion: In conclusion, fracture consolidation with two cannulated screws is an effective approach for the treatment of osteosynthesis of femoral neck fractures. Keywords: Femoral neck fractures, Osteosynthesis, two cannulated screws, three cannulated screws.